Relationship ideals in Charles Dickens’ Great Expectations - Shahizah Hamdan,; Dinnur Qayyimah Ahmad Jalaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Our main argument for examining romantic relationships in Charles Dickens’ Great Expectations rests on the fact that although thematically it can be said that the novel focuses on class structure, the thrust of the plot centres on a number of relationships. The Victorian era was an age of change. With the expansion of the empire and the progress brought about by the industrial revolution, new ways of thinking started to influence the society and its culture. This included ideals on relationships and marriages. To establish our problem statement, we refer to the work Romance’s Rival: Familiar Marriage in Victorian Fiction by Talia Schaffer. According to Schaffer, a Victorian woman may marry for romance or she may marry for practical reasons. Based on long-established Victorian norms, we hypothesise that romantic marriages will result in unmet expectations. To support this hypothesis we adapted Vannier and O’Sullivan’s investment model framework to analyse the relationships in Great Expectations. We also widened the scope to include analysis of male characters involved in the relationships. As there was no clear pattern with regards to romantic relationships, we posit that even in the Victorian age, relationship expectations, ideals and success are determined by individual personalities and perceptions and not by social norms or expectations.